AI-Driven Optimization of Intelligent Supply Chains and Payment Systems: Enhancing Security, Tax Compliance, and Audit Efficiency in Financial Operations - Harish Kumar Sriram (Mathematical Statistician and Engineering Applications, 2022)
The potential of Artificial Intelligence (AI) to impressively improve logistics and supply chains has long been recognised. However, only in recent years have the resources and accomplishments in AI research become available to efficiently engage in the kind of optimisation required by modern and intelligent supply chains and payment systems. In view, with the rise of the Internet of Things (IoT), vehicle routing, Big Data, and blockchain-driven track and trace, effective and ongoing application of a new sub-field, AI-driven optimization, is seen as the next key challenge and productivity improvement for the structure and design of future-risk-averse intelligent logistics. Therefore, as a perspective of multiple interrelated novel standing points of view a broad introduction to this field is given here. The benefits of AI technology will be comprehensive and balanced to successfully fulfill such an optimized concept of future intelligent logistics and accompanying payment systems, particularly if along with the technical aspects its strong social and environmental impacts are closely monitored and controlled. Hence, increasing the transparency, explainability, and resilience of the AI and AI-guided approaches will be relevant competitive advantages. If the upcoming breakthroughs in the field of AI-driven optimization of logistics and supply chains are to be established, significant new forms of collaboration between businesses, authorities, and academia is vital. As a starting point for such comprehensive interaction, highlighted by the missing cross-sector or cross-field interdisciplinary efforts on this topic thus far, an appropriate research agenda, as well as significant spaces for joint R&D projects, are proposed and identified.